First experiences with negative pressure wound therapy and instillation in the treatment of infected orthopaedic implants: a clinical observational study - Lehner, Burkhard; Fleischmann, Wim; Becker, Rolf; Jukema, Gerrolt N. (International orthopaedics, 2011)
Purpose Infections associated with orthopaedic implants remain a serious complication. The main objective in acute infection control is component retention, whereas this option is usually not considered for chronic infections. Methods This multi-centre prospective, non-randomised observational study investigated one possible treatment option for implant retention in combination with negative pressure wound therapy with instillation (NPWTi). Thirty-two patients with an infected orthopaedic implant were analysed. Twenty-two patients had an acute infection (< 8 weeks after implantation) and ten patients had a chronic infection (> 8 weeks and < 36 weeks after implant placement). Polyhexanide was used as the instillation solution in 31 of the 32 cases. Results Nineteen patients (86.4%) with an acute infection and eight patients (80%) with a chronic infection retained their implant at 4-6 months follow-up after treatment. Conclusions Our study showed that NPWTi can be used as adjunctive therapy for salvage of acutely infected orthopaedic implants and may even be considered for early chronically infected implants.